Rural public library in developing a nation: Case study of Malaysian and Australian rural public library - Abu, Roziya; Abdul Malik, Anis Faradella; Azmi, Nor Azlina (2014)
A rural library is a library or library system that serves a rural community or population that primarily lives on farms and ranches, and in remote communities. Genuinely, the guidelines for a good rural library creation and operation is that: the rural library should not solely be based on the provision of printed materials and that the rural library should be rooted in the community and for the most part, facilitated by members of that particular community.In Malaysia and Australia, rural development has always been the focus of the local government.A variety of facilities and infrastructure were built to support the process of the rural community social and economic development; rural public libraries are one of these facilities.The purpose of this paper is to discuss the initiatives of development activities and programs that underpin rural public libraries in supporting rural community development in Malaysia and in Australia.The discussing of the initiatives will be base on cross-case analysis findings in three rural public libraries in Selangor, Malaysia and three rural public libraries in Victoria, Australia.